The journey from stem cell to macrophage - Pittet, Mikael J. (2014)
Essential protectors against infection and injury, macrophages can also contribute to many common and fatal diseases. Here we discuss the mechanisms that control different types of macrophage activities in mice. We follow the cells’ maturational pathways over time and space, and elaborate on events that influence the type of macrophage eventually settling a particular destination. The nature of the precursor cells, developmental niches, tissues, environmental cues, and other connecting processes appear to contribute to the identity of macrophage type. Together, the spatial and developmental relationships of macrophages comprise a topo-ontogenic map that can guide our understanding of their biology.